An unusual breast mass: primary synovial sarcoma. (19th June 2013) - Doyle, Victoria J; Bateman, Adrian C; Theaker, Jeffery M
Abstract : We describe a 54-year-old woman presenting with mastalgia and a 6 mm breast lesion on imaging. Core biopsy revealed a lesion characterised by a predominant epithelioid and a minor spindle cell component. Our differential diagnosis included intraduct papilloma/adenoma and adenomyoepithelioma. However, initial immunohistochemistry did not support these diagnoses and further immunohistochemistry raised the possibility of a synovial sarcoma. This was confirmed with the finding, using fluorescence in-situ hybridisation, of the characteristic translocation t(x; 18) (p11.2; q11.2) . Establishing a diagnosis of synovial sarcoma at unusual sites may be difficult, especially when limited tissue is available, for example, within a core biopsy. In this case, immunohistochemistry was useful, but cytogenetics was the key additional investigation. It is important to consider the possibility of rare tumours when the morphological and immunohistochemical features of a lesion initially appear conflicting or inconclusive.